‘Outside of everything and everybody’: renegotiating place in the classroom - Robinson, Joanna (Taylor and Francis, 2016)
This article examines a series of plays created by Nottingham Playhouse Roundabout Theatre in Education Company in the first years of the twenty-first century that aimed to respond to rising concerns about the impact of increasing numbers of refugees in the East Midlands. My discussion focuses on two of these: Mohammed, performed to Year 6 students (age 10-11) (Seligman, Nielsen and Larsen, 2003) and Mia, performed to Year 10 and 11 students (age 14-16) (Wood, 2004). Both plays, which toured to schools across Nottingham and Nottinghamshire, tackled the journeys made by individual asylum seekers from danger in other lands to the place of the school hall or classroom, and in doing so, they juxtaposed global geographies with the personal, local geographies of the pupils encountering the actors. This article places those encounters within a framework discussion of place and community that draws on insights from sociology, geography, and performance studies. It seeks to explore the different effects created in terms of Roundabout’s stated aim of effecting ‘positive attitude changes towards refugees, asylum seekers and any other people hitherto thought of as “different” because of their race, culture or religious beliefs’. Drawing on discussions of geographical and social space from Doreen Massey, Martin Albrow and Arjun Appadurai, the article argues that Roundabout opened up questions of place, identity and community for their student audience by an increasingly complex utilisation of the interrelationships between place and space – both the ‘local place’ of the school and its students and the mobile, unstable space of the protagonists’ own transitory lives as refugees – and the performance relationship between actor and audience.